EFEKTIVITAS KEGIATAN PENGAJIAN DALAM PEMBINAAN AKHLAK GENERASI MUDA DI PONDOK PESANTREN AL-BAROKAH DESA KUTANEGARA KECAMATAN CIAMPEL KABUPATEN KARAWANG - Wulan Handayani; Acep Nurlaili; Sayan Suryana (Universitas Islam Madura, 2023)
The social phenomenon of teenagers who do not pay attention to their attitude patterns, manners and morals in socializing in society is not good and is not following religious guidance, such as a lack of respect and respect for other people, which is possibly caused by the pattern of education they receive that is less than optimal. Added to this are the problems of the digital world/internet/gadgets which then take up a lot of their time in socializing, resulting in a lack of social activities and making teenagers become individualistic. Islamic religious education, which in this case is general recitation, exists to overcome this problem. Lack of understanding of religious education causes them to experience moral and moral decline. This phenomenon makes researchers interested in conducting research on this theme. The research method used is qualitative with a phenomenological type with informants being education practitioners and people who are considered to be related to the phenomenon. The research results show that Islamic religious education in forming the morals of the younger generation has been used well based on the aspects of time, understanding, convenience and interest in forming morals. They can also use this Islamic religious education activity well because it can be used as a guide for their life. The implication of the results of this research is that teenagers can easily understand Islamic religious knowledge, which can have implications for their social patterns and behavior in society. The patterns and behavior of teenagers can be better and more ethical.